2018
DOI: 10.3389/fpsyg.2018.01999
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Language Oscillogenome

Abstract: Language has been argued to arise, both ontogenetically and phylogenetically, from specific patterns of brain wiring. We argue that it can further be shown that core features of language processing emerge from particular phasal and cross-frequency coupling properties of neural oscillations; what has been referred to as the language ‘oscillome.’ It is expected that basic aspects of the language oscillome result from genetic guidance, what we will here call the language ‘oscillogenome,’ for which we will put for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 304 publications
(349 reference statements)
0
21
0
Order By: Relevance
“…We have good accounts of the genetic and epigenetic changes which occurred after our split from Neanderthals that plausibly account for the emergence of important aspects of our language-readiness (see Boeckx and Benítez-Burraco, 2014a,b and Benítez-Burraco and Boeckx, 2015 for review). We certainly lack confident translations of these changes to the sort of cognitive abilities that are needed for acquiring and mastering a language (but see Murphy and Benítez-Burraco, 2018a,b for some accounts). Regarding the cultural niche that enables (and fosters) language complexity and the acquisition of language by the child, different hypotheses have been launched about its nature and origins.…”
Section: Introductionmentioning
confidence: 99%
“…We have good accounts of the genetic and epigenetic changes which occurred after our split from Neanderthals that plausibly account for the emergence of important aspects of our language-readiness (see Boeckx and Benítez-Burraco, 2014a,b and Benítez-Burraco and Boeckx, 2015 for review). We certainly lack confident translations of these changes to the sort of cognitive abilities that are needed for acquiring and mastering a language (but see Murphy and Benítez-Burraco, 2018a,b for some accounts). Regarding the cultural niche that enables (and fosters) language complexity and the acquisition of language by the child, different hypotheses have been launched about its nature and origins.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of models have been proposed to explain the implementational basis of hierarchical phrase structures (reviewed in Aboitiz, 2017; Friederici, 2017). A range of paleoanthropological, paleoneurological and genetic data has also been consulted in an effort to map out an accurate path that language evolution likely took (Zollikofer and Ponce de León, 2013; Benítez-Burraco and Boeckx, 2015; Beaudet, 2017; Murphy and Benítez-Burraco, 2018a, b). My intention here is to review some possible connections between these distinct modes of inquiry by exploring a specific set of phenotypic traits and evolutionary processes which have the potential to explain the emergence of core features of language such as syntactic complexity and unrestricted semantic combinatorics.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of PVALB-expressing GABAergic interneurons results in complex behavioral changes related to the behavioral phenotype of people with SZ (Brown et al, 2015). Importantly, some of the key changes that contributed to the emergence of our language-readiness involved GABAergic signaling (discussed in detail in Boeckx and Benítez-Burraco, 2014b), which are vital for oscillatory processes underlying language processing (Bae et al, 2010; see Murphy and Benítez-Burraco, 2018 for details). Reduction in PVALB expression in interneurons has also been found in mouse models of ASD (Filice et al, 2016), specifically, in the Cntnap2-/- model (Lauber et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding LIMK1 , it regulates synaptic plasticity and long-term memory (Todorovski et al, 2015), and its hemideletion has been hypothesized to account for the observed deficits in spatial cognition in combination with other genes (Gray et al, 2006; Smith et al, 2009). Still, these potential links with aspects of language (dys)function seem quite vague, particularly if one considers our remarkable understanding of the genetic underpinnings of human language, language disorders, and language evolution (see Scharff and White, 2004; Li and Bartlett, 2012; Benítez-Burraco, 2013; Graham et al, 2015; Fisher, 2017; Murphy and Benítez-Burraco, 2017, 2018 for reviews). Examining how robust candidate genes for language disorders and language evolution behave in people with WS should help refine our view of the molecular causes of the language deficits attested in this condition.…”
Section: Introductionmentioning
confidence: 99%